2005
DOI: 10.1007/11422778_89
|View full text |Cite
|
Sign up to set email alerts
|

Penalty Shaper to Enforce Assured Service for TCP Flows

Abstract: Abstract. Many studies have explored the TCP throughput problem in DiffServ networks. Several new marking schemes have been proposed in order to solve this problem. Even if these marking schemes give good results in the case of per-flow conditioning, they need complex measurements. In this paper we propose a Penalty Shaper (PS) which is able to profile a set of TCP flows so as to improve its conformance to a desired target. The main novelty of this shaper is that the shaping applies a penalty delay which depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The behaviour of these traffic conditioners have a great impact on the service level, in terms of bandwidth, obtained by TCP flows. Several others conditioners have been proposed to improve throughput insurance [10][11][12][13][14][15][16]. In all these articles, it is clearly shown that the key of the TCP throughput guarantee problem is the values 3-uple (loss probability, RTT, target rate) of a TCP flow.…”
Section: Tcp Over Diffserv/af Classmentioning
confidence: 98%
“…The behaviour of these traffic conditioners have a great impact on the service level, in terms of bandwidth, obtained by TCP flows. Several others conditioners have been proposed to improve throughput insurance [10][11][12][13][14][15][16]. In all these articles, it is clearly shown that the key of the TCP throughput guarantee problem is the values 3-uple (loss probability, RTT, target rate) of a TCP flow.…”
Section: Tcp Over Diffserv/af Classmentioning
confidence: 98%
“…As for TCP in the AF class [11], the TFRC mechanism is not aware that the loss was of an out-of-profile packet and that it should not decrease its actual sending rate below the target rate. For TCP, the solution was to introduce a conditioner able to better mark the TCP flows by taking into account the sporadic nature of the TCP flows [12], [13]. But the proposed conditioners are not all really efficient in certain network conditions, such as long RTTs, and are sometimes complex to use.…”
Section: A Problem Statementmentioning
confidence: 98%
“…Finally, as opposed to the marking strategy adopted by new conditioners, we have proposed a delay based shaper [26]. This shaper applies a delay penalty to a flow if there are outprofile packets losses in the network and if it outperforms its target rate.…”
Section: B Aimd Penalty Shapermentioning
confidence: 99%